Tensile strengths of flocculated compacted unsaturated soils. Issue 4 (29th October 2015) - Beckett, C. T. S.; Smith, J. C.; Ciancio, D.; Augarde, C. E.
Abstract : Flocculating agents can be introduced to soils through a number of natural or anthropogenic processes. This paper investigates the effect of flocculant addition (aqueous calcium chloride (CaCl2 )) on the tensile strengths of two soils of differing flocculation susceptibility. Tensile strengths were found using the Brazilian (direct splitting) test for a range of suction values. A decrease in tensile strength was found for a soil with high clay content, which was consistent with previous findings in the literature. However, the strength of the soil with lower clay content unexpectedly increased. Results were interpreted using the extended Mohr–Coulomb (EMC) yield criterion fitted to data above the residual suction value. Changes in EMC parameters were used to infer changes in material behaviour on calcium chloride addition. Results have important implications for the design of geotechnical structures, for example engineered cover systems, exposed to flocculating conditions.